(untitled) - 1922-2018.; Lee, Stan; 1930-; Harris, Rosemary; 1978-; Molina, Alfred; Franco, James; 1982-; Dunst, Kirsten; 1975-; Maguire, Tobey; 1953- (Culver City, Calif., 2004)
Peter Parker, a.k.a. Spider-Man, is desperately trying to balance his dual identities. He cant keep up at college, pay his rent or seem to make amends with his estranged best friend Harry. Mary Jane is more skeptical than ever of Peter. One day Peters idol, the renowned scientist Otto Octavius, resurfaces after a failed science experiment. Peter begins to notice hes losing some of his powers and wonders at the stress in his personal life. He realizes he must decide between being who he once was or retaining his secret identity to stop "Doc Ock" and save New York City from destruction.
The women of Spider-man.
Keywords: Lee, Stan; 1922-2018; Film adaptations; Ditko, Steve; Film adaptations; Drama; Conduct of life; College students; Drama; Crime prevention; Drama; Spider-Man (Fictitious character); Citizen participation; DVD-Video discs; Films for the hearing impaired; Spider-Man films; Science fiction films; Action and adventure films; Feature films; Video recordings for the hearing impaired